THE RELATIONSHIP BETWEEN HUSBANDS’ SUPPORT AND WIVES’ SUCCESS IN EXCLUSIVE BREASTFEEDING - Atika Zahria Arisanti; Anjar Ratnasari Winjaya (Journal of Advanced Nursing and Health Sciences, 2026)
Background: Breast milk is the primary source of nutrition for newborns and plays a crucial role in reducing infant mortality rates worldwide. Deaths among children under five years of age can be prevented each year through optimal breastfeeding. Spousal support is believed to be one of the key factors determining the success of exclusive breastfeeding. This study aims to analyze the relationship between a husband’s support for his wife’s efforts to practice exclusive breastfeeding at Sultan Agung Islamic Hospital in Semarang.Methods: This study employed a quantitative cross-sectional research design. The study subjects consisted of 55 primiparous mothers with 6-month-old infants at Sultan Agung Islamic Hospital in Semarang who met the inclusion and exclusion criteria. Sampling was conducted using total sampling. Data were collected using the G-Form questionnaire, which had been tested for validity and reliability. The data were analyzed using the chi-square test.Results: The results showed a significant relationship between spousal support and exclusive breastfeeding, with a p-value of 0.000 (p < 0.05). It is hoped that this study can provide useful information regarding the importance of the husband’s role in supporting the success of exclusive breastfeeding. It is also hoped that the public will become increasingly aware that breastfeeding is not only the mother’s responsibility but also requires active support from the husband and family.Conclusion: Education based on the results of this study can reinforce positive behaviors in breastfeeding practices.